Entospasyo Nueva Ecija Facility for edible insect research and mass production - Benedicto, Mikael Marlthel T.; Chua, Johannes Vincent F. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Humans have benefited from insects for thousands of years. With growing problems in food sustainability and climate change, it is necessary to take steps into addressing these growing issues. This projects aimed to create the need for a new agro-industry, nurture awareness and advocacies for its values, and evidently advance its potentials and growth through sustainable design and application. The possibility of a new building typology by integrating existing and emerging insect-rearing technologies is explored. In the design development, different design interventions were formulated to revitalize entomophagy in the local rural community which combined three main functions: research, production, and tourism. Along with site selection analysis, micro and macro site analysis, industry analysis and user analysis; key informant interviews and site visits supplemented the data gathered to formulate the design goals of the project. Guided by the concepts of modularity, immersion, and flexibility, a facility for edible insect research and mass production is seen as the appropriate architectural solution to address the need to promote insect rearing, and revitalize entomophagy in the local rural community.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Entomophagy -- Facility design